Waiting for Pushkin : Russian fiction in the reign of Alexander I (1801-1825) - Tosi, Alessandra (Studies in Slavic literature and poetics, 2006)
Waiting for Pushkin provides the only modern history of Russian fiction in the early nineteenth century to appear in over thirty years. Prose fiction has a more prominent position in the literature of Russia than in that of any other great country. Although nineteenth-century fiction in particular occupies a privileged place in Russian and world literature alike, the early stages of this development have so far been overlooked. By combining a broad historical survey with close textual analysis the book provides a unique overview of a key phase in Russian literary history. Drawing on a wide rang.